2008
DOI: 10.3892/or.19.2.505
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory effect of Fms-like tyrosine kinase 3 ligand on peripheral monocyte-derived dendritic cells and natural killer cells: Utilization for ovarian cancer treatment

Abstract: Abstract. Systemic administration of Fms-like tyrosine kinase 3 ligand (FLT3L) has been considered to be a major route of delivery for tumor immunotherapy because expression of its receptor, FLT3, was detected predominantly in hematopoetic progenitor cells. However, several studies indicate that FLT3L locally overexpressed in tumor or dendritic cells (DCs) also shows an anti-tumor effect. In the current study, we found that FLT3 expression is not present in monocytes but is instead induced in DCs through the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…Finally, FLT3 mutations are the most frequent genetic aberrations that have been described in acute myeloid leukemia (43). Importantly, FLT3 expression was not detected on monocytes, which sometimes contaminate purified T cells (not shown), in accordance with a recent report (44). Moreover, the staining obtained with EOL-1, a leukemia cell line known to express FLT3, although stronger than on activated T cells, was also low (not shown).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, FLT3 mutations are the most frequent genetic aberrations that have been described in acute myeloid leukemia (43). Importantly, FLT3 expression was not detected on monocytes, which sometimes contaminate purified T cells (not shown), in accordance with a recent report (44). Moreover, the staining obtained with EOL-1, a leukemia cell line known to express FLT3, although stronger than on activated T cells, was also low (not shown).…”
Section: Discussionsupporting
confidence: 92%
“…A total of three patients (two with mesothelioma and one with gastrointestinal cancer) had stable disease for 8, 8, and 12+ months, respectively. In another study, Flt-3L was tested as an adjuvant for HER-2/neu peptide-based vaccines in 10 patients with breast or ovarian cancers that overexpressed HER-2/neu [213] with the objective of finding out whether Flt-3L could be used systemically as a vaccine [214,215]. It has also been shown that Flt-3L acts synergistically with GM-CSF to induce the mobilization of hematopoietic stem cells and progenitor cells [216].…”
Section: Fms-like Tyrosine Kinase-3 Ligandmentioning
confidence: 99%
“…No [209][210][211][212][213][214][215][216][217] , MART- , and tyrosinase 368-376 with Montanide ISA 51 and i) IL-12 at 30 ng/kg with alum (group A), ii) IL-12 at 100 ng/kg with alum (group B), or iii) IL-12 at 30 ng/kg with 250 µg GM-CSF (group C). Mild toxicity was observed but it resolved rapidly.…”
Section: Alum Mf59 and Qs21mentioning
confidence: 99%
“…In the same system, myeloid DCs were expanded more than lymphoid DCs unlike that of murine system. In addition, studies showed anti‐tumor activity of FL via its ability to increase the production of both DCs and NK cells in vivo (Matsumura et al, ). Although the beneficial effects of FL on monocyte‐derived DCs (moDC) had been documented (Hubert et al, ), its role on monocytes or monocyte‐derived dendritic cells and the underlying mechanism of FL‐induced DCs activation have not been fully understood.…”
mentioning
confidence: 99%